Is GNB3 C825T polymorphism associated with elite status of polish athletes? - Sawczuk, M.; Maciejewska-Karlowska, A.; Cieszczyk, P.; Leonska-Duniec, A. (Biology of Sport, 2014)
The GNB3 gene encodes the beta 3 subunit of heterotrimeric G-proteins that are key components of intracellular signal transduction between G protein-coupled receptors (GPCR) and intracellular effectors and might be considered as a potential candidate gene for physical performance. Objectives: The aim of this study was to compare frequency distribution of the common C to T polymorphism at position 825 (C825T) of the GNB3 gene between athletes and nonathletic controls of the Polish population as well as to compare the genotype distribution and allele frequency of C825T variants within a group of athletes, i.e. between athletes of sports of different metabolic demands and competitive levels. Methods: The study was performed in a group of 223 Polish athletes of the highest nationally competitive standard (123 endurance-oriented athletes and 100 strength/power athletes). Control samples were prepared from 354 unrelated, sedentary volunteers. Results: The test revealed no statistical differences between the endurance-oriented athletes and the control group or between sprint/strength athletes and the control group across the GNB3 825C/T genotypes. There were no male-female genotype or allele frequency differences in controls or in either strength/power or endurance-oriented athletes. No statistically significant differences in either allele frequencies or genotype distribution were noted between the top-elite, elite or sub-elite of endurance-oriented and strength/power athletes and the control group. Conclusions: No association between elite status of Polish athletes and the GNB3 C825T polymorphic site has been found.